Impact of once-versus twice-yearly treatment of common soil-transmitted intestinal helminths (STH) on cognitive-functions of elementary school children in Binan, Laguna - Malecosio, Jr., Serafin O.
This randomized experimental study was conducted primarily to compare the effects of once- versus twice-yearly anthelmintic treatment of common soil-transmitted helminth (STH) infections on cognitive-functions of elementary school children in Binan, Laguna. Secondarily, it aimed to compare the baseline cognitive-function test scores of pupils in terms of the following: (1) STH infected vs. non-infected; (2) negative-to-light vs. moderate-to-heavy intensity of STH infections; (3) mixed infections of Ascaris and Trichuris vs. single infections of either Ascaris or Trichuris.Grade III pupils, the study population, were randomly assigned into two treatment groups: Groups I and II. Group I received once-yearly treatment, while Group II received twice-yearly treatment. Forty-six (46) pupils, with ages below nine years and six months at baseline, were randomly selected from each treatment group. A total of ninety-two (92) pupils were selected as study participants.Fecal specimens of the study population were collected. The specimens were then processed using the Kato-Katz smear technique and were examined under the microscope to determine the prevalence and the intensity of STH infections at baseline.The baseline cognitive-function tests were administered to 92 study participants. The Philippine Indigenized Pre-school and Primary Intelligence Test (PIPPIT) was used as test instrument. The test is composed of verbal and performance tests, with frou sub-tests in each component. Eight interns "(3rd year BS Psychology students) from Philippine Normal University (PNU) administered the tests both at baseline and at repeat tests. They were trained and assisted by a psychologist.A single dose of 500 mg mebendazole was given to 92 study participants after baseline test administration. Six-months after the first treatment, the second dose of 500 mg mebendazole and placebo tablet were given to forty-six (46) pupils of the twice-yearly treatment group (Group II) and forty-six (46) pupils of once-yearly treatment group (Group I), respectively. The repeat cognitive-function test was then administered to Groups I and II, 2-3 weeks after the second treatment. The same interns administered the same set of test.Independent t-test for unequal sample size revealed the following significant results at baseline: (1) the STH infected group was found to have significantly poorer scores in vocabulary (p=0.030), discrimination ability (p=0.006), memory (p=0.047), overall performance test (p=0.037), and total score (p=0.037) comapred with the non-infected group; (2) the moderate-to-heavy Ascaris infections was found to have significantly poorer mean logical reasoning test score compared with the negative-to-light intensity (p=0.018); (3) to moderate-to-heavy Trichuris infections was found to have significantly poorer mean overall verbal test score compared with negative-to-light intensity (p=0.042).One-way analysis of variance (ANOVA) revealed that there was no sufficient evidence to show that pupils with mixed infections of Ascaris and Trichuris had significantly lower cognitive-function test scores compared to those harboring single infections of either Ascaris or Trichuris.It seems that the twice-yearly treatment group reduced the prevalence and intensity of infections better than the once-yearly treatment group. Consequently, the twice-yearly treatment group had obtained marked percent increase in four specific verbal ability tests (comprehension, vocabulary, numerical ability, and concept formation) as well as in general or over-all veral mean scores compared with the once-yearly treatment group.
However, multiple regression analysis showed that there was no sufficient evidence to conclude that the twice-yearly treatment improved significantly the cognitive-function of children compared with the once-yearly treatment taking into account the difference of the intensity of infections between the two treatment groups. The results suggests that the 2-3 weeks interval after treatment may not have been enough to cause significant improvement in nutritional, blood iron, and hematological factors of children that would merit significant change on cognitive-functions.Future studies should select only the study participants with moderate-to-heavy intensity of STH infections for it is known that this intensity of infection cause significant adverse effects on cognitive-functions of children. The repeat cognitive-function tests shall be administered at least 10 weeks after the second treatment to permit significant change in nutritional, iron and hematological status of children. In view of the findings, this study also recommends the immediate treatment of school children to help them fully benefit from primary education.
Thesis (Master of Science in Public Health, Parasitology)--University of the Philippines Manila.
Keywords: Soil-transmitted intestinal helminths; Children -- Cognition